2022
DOI: 10.3390/biology11040537
|View full text |Cite
|
Sign up to set email alerts
|

Initial Muscle Quality Affects Individual Responsiveness of Interleukin-6 and Creatine Kinase following Acute Eccentric Exercise in Sedentary Obese Older Women

Abstract: This study aimed to evaluate the time course and responsiveness of plasma interleukin-6 (IL-6) and creatine kinase (CK) levels following acute eccentric resistance exercise in sedentary obese older women with a different muscle quality index (MQI). Eighty-eight participants (69.4 ± 6.06 years) completed an acute eccentric resistance exercise (7 sets of 10 repetitions at 110% of 10-repetition maximum with 3 min rest interval). Participants were divided into two groups: high or low MQI according to 50th percenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Fifteen studies reported the acute effect of resistance exercise on circulating muscle proteins (Table 6 ). Four of these studies were conducted exclusively in females [ 50 , 61 63 ], seven were conducted in males [ 45 , 46 , 49 , 55 , 56 , 64 , 65 ], and four were conducted with a mixed sample [ 57 , 58 , 66 , 67 ]. Seven of the studies included a younger group of adults for comparison [ 45 , 46 , 49 , 50 , 57 , 58 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies reported the acute effect of resistance exercise on circulating muscle proteins (Table 6 ). Four of these studies were conducted exclusively in females [ 50 , 61 63 ], seven were conducted in males [ 45 , 46 , 49 , 55 , 56 , 64 , 65 ], and four were conducted with a mixed sample [ 57 , 58 , 66 , 67 ]. Seven of the studies included a younger group of adults for comparison [ 45 , 46 , 49 , 50 , 57 , 58 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the studies included a younger group of adults for comparison [ 45 , 46 , 49 , 50 , 57 , 58 , 66 ]. Eleven of the studies involved an eccentric exercise protocol [ 45 , 46 , 50 , 56 58 , 61 63 , 65 , 66 ], three of which were solely using elbow flexors [ 45 , 46 , 50 ], one used an eccentric-concentric protocol of the knee extensors [ 66 ]. The remainder used concentric protocols involving the whole body or lower limbs [ 49 , 55 , 64 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that IL-6 can induce GLUT4 translocation to the cell membrane in response to insulin-stimulated glucose disposal, and it can also improve glucose tolerance, possibly through the AMPK signaling pathway [ 78 80 ]. Several studies have reported eccentric exercise-mediated IL-6 release, which might serve as a possible link between eccentric training-related systemic adaptation and metabolic processes [ 81 83 ]. However, there is a controversy in the literature whether the magnitude of IL-6 response is more significant in eccentric exercise.…”
Section: Eccentric Contraction-induced Changes In Myokine Productionmentioning
confidence: 99%
“…14 Therefore, MQ could help health professionals design better rehabilitation programs to enhance independence in the aging population. 15 In applied research settings, field-based estimates of MQI (dividing handgrip strength by upper limb muscle mass, body weight, or BMI) provide a similar prediction for mobility and lower extremity performance in communitydwelling older adults when compared to the most expensive method to determine MQI (eg, laboratory, normalized by lean mass through dual-energy x-ray (DXA)). 16 In our laboratory, we observed a strong correlation effect between field MQI and laboratory MQI in octogenarians, which highlights the importance of simpler measures.…”
Section: Introductionmentioning
confidence: 99%